(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
The objective of this article is to reflect on how the visual arts can be a starting point for theatrical creation, and to show that through this relationship with the visual arts, theatre students become capable of reflecting and understanding the field of visualities of the scene, seeking new ways of expressing oneself and understanding the power and influence of scenic characterization, an aspect that enriches the actor’s work in the interpretation, because by permeating the field of visualities of the scene, the actor better understands his character.